2022
DOI: 10.1097/rli.0000000000000848
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Contrast Enhancement and Virtual Monoenergetic Image Energy Levels on Emphysema Quantification

Abstract: The aim of this study was to evaluate the impact of contrast enhancement and different virtual monoenergetic image energies on automatized emphysema quantification with photon-counting detector computed tomography (PCD-CT). Material and Methods: Sixty patients who underwent contrast-enhanced chest CT on a first-generation, clinical dual-source PCD-CT were retrospectively included. Scans were performed in the multienergy (QuantumPlus) mode at 120 kV with weight-adjusted intravenous contrast agent. Virtual nonco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 60 publications
2
26
0
2
Order By: Relevance
“…For PCD-CT, there are only a few studies evaluating the use of VMI, for example in the quantification of emphysema [28] or in the determination of the lowest possible iodine contrast concentration [30]. In line with previous studies, image noise increased with decreasing VMI energy in our study [28].…”
Section: Discussionsupporting
confidence: 88%
“…For PCD-CT, there are only a few studies evaluating the use of VMI, for example in the quantification of emphysema [28] or in the determination of the lowest possible iodine contrast concentration [30]. In line with previous studies, image noise increased with decreasing VMI energy in our study [28].…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies have investigated the value of VMIs for e.g. CT angiography of the aorta, contrast-enhanced abdominal CT, musculoskeletal imaging and emphysema quantification [17][18][19][20]. To our knowledge, there are no studies regarding the potentially improved conspicuity of hypovascularized liver metastases.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have found substantially increased image noise for VMI at 40 and 50 keV [ 33 , 34 , 35 ]. The authors noted that VMI 70 keV were subjectively preferred [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have found substantially increased image noise for VMI at 40 and 50 keV [ 33 , 34 , 35 ]. The authors noted that VMI 70 keV were subjectively preferred [ 33 , 34 , 35 ]. Similarly, in our study the subjective assessment of image noise was best at VMI energy 70 keV.…”
Section: Discussionmentioning
confidence: 99%